Re-exploration following caesarean birth: a prospective national case-control study using the United Kingdom Obstetric Surveillance System (UKOSS) data collection system - Bhatia, K; Columb, M; Knight, M; Vause, S (Wiley, 2024)
Background: Re-exploration following caesarean birth and the associated maternal morbidity has not been investigated in the UK. Our aims were to determine the national incidence and identify the associated risk factors. Methods: We conducted a prospective observational case–control study across 194 UK consultant-led maternity units in women whose caesarean birth was complicated by a re-exploration. Independent factors for re-exploration were analysed using multivariable multi-level mixed effects logistic regression. Results: Over the study period (1 June 2021 and 31 May 2022) 238,423 caesarean births were recorded across the UK of which 187 women underwent re-exploration, giving an incidence of one re-exploration per 1282 caesarean births (95%CI 1:1099–1:1471). Haemorrhage (124/187, 66.3%) and sepsis (31/187, 16.6%) were the most common findings at re-exploration. Median (IQR [range]) time interval to re-exploration following the caesarean birth was 1 (0–4 [0–28]) day. Mechanical ventilation was required in 34 (18.6%) women, cardiac arrest was reported in 5 (2.7%) and 3 (1.6%) women died. Independent preceding factors associated with a re-exploration included: receipt of blood transfusion (adjusted OR (95%CI) 8.25 (2.66–25.61)); use of a general anaesthetic (adjusted OR (95%CI) 3.33 (1.61–6.88)); pre-eclampsia (adjusted OR (95%CI) 3.27 (1.55–6.91)); black ethnicity (adjusted OR (95%CI) 3.14 (1.39–7.11)); postpartum haemorrhage (adjusted OR (95%CI) 2.82 (1.81–4.37)); use of anticoagulants or antiplatelet drugs pre-caesarean birth (adjusted OR (95%CI) 2.26 (1.35–3.81)); and emergency caesarean birth (adjusted OR (95%CI) 1.89 (1.01–3.57)). Conclusion: Re-exploration following caesarean birth in the UK is uncommon but is associated with significant maternal morbidity and mortality. These study findings will help guide informed consent and encourage appropriate surveillance of high-risk women postpartum.